La Eneida de Virgilio, un viaje entre Troya y Roma - Cristóbal, Vicente (Revista de Filología Románica, 2006)
In the Aeneid the Aeneas’ journey is only a brief sequence of a longer and more relevant travel through time, a travel that covers the distance between the legendary Troy and the historical Rome, which is the real argument of the Vergilian epic.